Effect of ramie fibre on mechanical properties of lightweight foamed concrete / Md Azree Othuman Mydin - Othuman Mydin, Md Azree (Universiti Teknologi MARA Shah Alam, 2022)
Lightweight foamed concrete (LFC) is good in compression but poor in tension, as it produces multiple microcracks. LFC cannot withstand the tensile stress induced by applied forces without additional reinforcing elements. This study was conducted to assess the potential utilisation of ramie fibre reinforced LFC in terms of its mechanical properties. Density of 600 kg/m3 was cast and tested with 4 different weight fractions of ramie fibre, which were 0.2, 0.4, 0.6 and 0.8 %. The mechanical properties examined were compressive strength, flexural strength and tensile strength. The results revealed that the addition of 0.6 % of ramie fibre into LFC aids to give the best results for the compressive strength, flexural strength and splitting tensile strength. The existence of ramie fibre in LFC facilitated in evading the promulgation of cracks in the plastic state in the cementitious matrix when the load was applied.